Pengembangan Laboratorium Virtual sebagai Media Pembelajaran: Peluang dan Tantangan - Kurnia Muhajarah; Moh. Sulthon (Unversitas Muhammadiyah Mataram, 2020)
Abstract: Laboratory is a learning resource and learning media. The purpose of this research is what is the urgency of the laboratory as a learning medium and what are the opportunities and challenges of the virtual laboratory as a pedagogical framework overview. Therefore, researchers are interested in conducting studies on this matter. This research uses library research and is qualitative in nature. The result of this research is a laboratory as a place for activities that are needed in practice, which is often used as a standard for student success. Virtual laboratories have a significant impact in terms of preparing students for real-world experiences, as well as savings in equipment procurement and maintenance costs, flexibility in location, study time and practical use Abstrak: Laboratorium merupakan salah satu sumber belajar dan media pembelajaran. Tujuan dari penelitian ini adalah bagaimanakah urgensi laboratorium sebagai media pembelajaran dan bagaimanakah peluang dan tantangan laboratorium virtual sebagai sebuah pedagogical framework overview. Oleh karena itu peneliti tertarik untuk melakukan kajian mengenai hal ini. Penelitian ini menggunakan jenis penelitian kepustakaan dan bersifat kualitatif. Hasil penelitian ini adalah laboratorium sebagai tempat kegiatan yang dibutuhkan dalam praktek, seringkali dijadikan standar kesuksesan mahasiswa. Laboratorium virtual mempunyai dampak signifikan dalam hal mempersiapkan mahasiswa untuk menghadapi pengalaman nyata, juga penghematan biaya pengadaan dan perawatan alat, fleksibilitas lokasi, waktu belajar dan praktek.